Understanding the Construct of Maximizing Tendency: A Theoretical and Empirical Evaluation. (19th March 2015) - Dalal, Dev K.; Diab, Dalia L.; Zhu, Xiaoyuan ( Susan); Hwang, Timothy
Abstract: More attention is being given to the stable, dispositional tendency to maximize when making decisions. Within the growing body of research has been an exchange regarding the appropriate means of measuring maximizing tendency. Guided primarily by psychometric and statistical analyses, these studies have critiqued and revised existing maximizing tendency scales and/or introduced new measures. Importantly, many of these discussions seem to ignore theoretical considerations of the construct of maximizing. In this article, we revisit the original work of Herbert Simon, from where the theory of maximizing tendency was developed, and provide a theoretical account for how maximizers can be distinguished from satisficers and the implications therein for the measurement of maximizing tendency. Across two studies, we provide an updated psychometric, correlational, and behavioral comparison of the two most popular maximizing tendency scales: the Maximization Scale and the Maximizing Tendency Scale. Results demonstrate that the Maximizing Tendency Scale is more theoretically and psychometrically valid than the Maximization Scale. Copyright © 2015 John Wiley & Sons, Ltd.